Assessment of the psychosocial impacts of cochlear implants on adult recipients and their partners. (3rd March 2016) - Chen, Stephen; Karamy, Babak; Shipp, David; Nedzelski, Julian; Chen, Joseph; Lin, Vincent
Abstract : Objectives : In the present study we sought to evaluate the psychosocial and quality of life (QOL) impacts of cochlear implant (CI) treatment on both CI recipients and their partners in a Canadian population. Methods : A qualitative cross-sectional contemporary cohort evaluation was conducted by distributing specifically designed questionnaires to both CI recipients and their partners at their follow-up appointments over a month at Sunnybrook Health Sciences Centre. Results : It was found that both CI recipients and their partners demonstrated substantial benefit and improvement in multiple psychosocial domains. Discussion : Musical listening was found to show variable improvements between recipients. Further analysis found a simple correlation where the group of recipients who all had a hearing disability for a longer duration had demonstrated a higher proportion of improvement in musical listening. CI recipients endorsed having improved QOL which was in agreement with proxy observation by partners. Conclusion : Overall, CI use has been shown to have significant benefit to psychosocial well-being of CI recipients. This benefit is also conferred to their caregivers/partners; which in our society concerned about caregiver burden is quite important to recognize.